Vehicle Components Defect Detection via Machine Vision - Petrosyan, Armen S. (Mathematical Problems of Computer Science, 2021)
The task of quality control and automatic defect detection on production lines is one of the most important tasks of machine vision and digital image processing (DIP). This article provides one example of solving such a problem using various DIP algorithms.